Research on Cophase Power-Supply Technology Applying on Shenshuo Railway - GUO Jin-chao (机车电传动)
The basic theory of cophase power supply technology was introduced. Based on analysis of the present status and the expansion measure of Shenshuo railway transport capacity, power supply performance of Shenshuo railway, such as canceling electrical separation, using fully electricity power returning by locomotive, dynamic reactive compensation and harmonic suppression, were optimized after applying cophase power supply technology. The technical and economic comparison result showed that cophase power supply technology not only could expand transport capacity of Shenshuo railway, but also had outstanding cost-effective and great value for application and extending.